Determination of Electronic and Ionic Partial Conductivities of BaCeO3 with Yb and In Doping - Choi, Sung Min; Lee, Jong-Heun; Choi, Moon-Bong; Hong, Jongsup; Yoon, Kyung Joong; Kim, Byung-Kook; Lee, Hae-Weon; Lee, Jong-Ho (ELECTROCHEMICAL SOC INC, 2015)
The total electrical conductivity of BaCeO3-based proton conductors with various dopants was measured using a DC-4 probe method. Yb and In were used as dopants to increase electrical conductivity and chemical stability, respectively. The electronic and ionic partial conductivities of samples of various compositions, i.e., BaCe1-x-yYbxInyO3-delta, where x = 0.1, y = 0.00, 0.05, and 0.10 (BC10Yb, BC10Yb05In, and BC10Yb10In, respectively) and x = 0.15, y = 0.00 (BC15Yb), were calculated based on the relevant defect chemistry model and interpreted as functions of fairly extensive ranges of P(O-2) (-4 <= log P(O-2) <= 0) and P(H2O) (-3.5 <= log P(H2O) <= 1.5) at 700 degrees C. The partial conductivities of all charge carriers, i.e., protons, holes, and oxygen vacancies, increased with Yb doping but decreased as In doping increased. The variations in the partial conductivity of holes and protons induced by the composition of doping constituents can be explained by the difference in electronegativity between dopant cations and oxygen anions as well as A- and B-site cations that are most critical in a general hopping conduction mechanism. Oxygen ion conductivity is controlled by the dopant size and content, which generally alter the lattice spacing and distortion of the perovskite structure. (C) 2015 The Electrochemical Society. All rights reserved.
Keywords: DEFECT STRUCTURE-ANALYSIS; FUEL-CELL APPLICATIONS; ELECTRICAL-CONDUCTIVITY; CHEMICAL-STABILITY; PROTON CONDUCTORS; TRANSPORT-PROPERTIES; SOLID-SOLUTIONS; BARIUM CERATE; OXIDES; ELECTROLYTES